Seasonal Variations in Seminal Characteristics of Shikabrown Breeder Cocks - Obidi, J.A.; Onyeanusi, B.I.; Rekwot, P.I.; Ayo, J.O.; Dzenda, T. (International Journal of Poultry Science, 2008)
The seasonal influence on the seminal characteristics of Shikabrown breeder cocks was evaluated weekly during the three seasons in Northern Guinea Savannah zone of Nigeria. Semen samples were analyzed by gross and routine laboratory methods for volume, motility, concentration, colour, percent dead and percent total abnormality. The highest volume and concentration values of 0.50 ± 0.03ml and 3.60 ± 0.16x109/ml, respectively, were obtained from Shikabrown White breeder cocks during the rainy season, while the lowest volume and concentration values of 0.39 ± 0.01ml and 2.90 ± 0.04x109/ml, respectively, were obtained for the same strain during the hot-dry season. Spermatozoa motility of 80.5 ± 1.1% and 82.3 ± 0.5% were obtained during the harmattan and rainy seasons, respectively, in Shikabrown White breeder cocks. Percent dead sperm values of 4.6 ± 8.3% and 6.40 ± 0.5% were recorded during the rainy and hot-dry seasons, respectively; which were lower (P < 0.05) than the value of 9.0 ± 1.0% obtained during the harmattan season in Shikabrown White breeder cocks. For the Shikabrown Red breeder cocks, spermatozoa volume and concentration were 0.44 ± 0.02ml and 3.44 ± 0.05x109/ml; while 0.45 ± 0.05ml and 3.53 ± 0.09x109/ml.were recorded for the harmattan and rainy seasons, respectively. These values were significantly (P < 0.01) different from the corresponding values of 0.30 ± 0.02ml and 2.50 ± 0.08x109/ml obtained for volume and concentration, respectively, during the hot-dry season in the Shikabrown Red breeder cocks. Percent dead sperm in the Shikabrown Red cocks during the rainy and hot-dry seasons (5.50 ± 1.0% and 6.20 ± 1.2%, respectively) were not statistically (P < 0.05) significant, but were significantly lower (P < 0.01) than the value of 8.40 ± 0.5% obtained during the harmattan season. The ejaculate trait for percent abnormality in Shikabrown Red cocks was not significantly different from that of the Shikabrown White strains. In conclusion, spermatozoa were recovered throughout the year and optimal gamete quality was observed during the rainy and harmattan seasons.